Design and Implementation of a Generic Energy-Harvesting Framework Applied to the Evaluation of a Large-Scale Electronic Shelf-Labeling Wireless Sensor Network. (27th July 2010) - De Mil, Pieter; Jooris, Bart; Tytgat, Lieven; Catteeuw, Ruben; Moerman, Ingrid; Demeester, Piet; Kamerman, Ad
Abstract : Most wireless sensor networks (WSNs) consist of battery-powered nodes and are limited to hundreds of nodes. Battery replacement is a very costly operation and a key factor in limiting successful large-scale deployments. The recent advances in both energy harvesters and low-power communication systems hold promise for deploying large-scale wireless green-powered sensor networks (WGSNs). This will enable new applications and will eliminate environmentally unfriendly battery disposal. This paper explores the use of energy harvesters to scavenge power for nodes in a WSN. The design and implementation of a generic energy-harvesting framework, suited for a WSN simulator as well as a real-life testbed, are proposed. These frameworks are used to evaluate whether a carrier sense multiple access with collision avoidance scheme is sufficiently reliable for use in emerging large-scale energy harvesting electronic shelf label (EHESL) systems (i.e., 12000 labels in a star topology). Both the simulator and testbed experiments yielded an average success rate up to 92%, with an arrival rate of 40 transceive cycles per second. We have demonstrated that our generic energy-harvesting framework is useful for WGSN research because the simulator allowed us to verify the achieved results on the real-life testbed and vice versa.